The EU climate strategy: Building blocks for international climate policy after 2012 - Susanne Dröge (Stiftung Wissenschaft und Politik (SWP), 2007)
On 10 January 2007, the European Commission introduced its new energy and climate change policy. This package of measures brings together diverse proposals put forward to the EU Council, which has convened in early March under the German Presidency to determine the goals of the EU's future climate change and energy policy. Since the time is growing short for negotiations on international climate policy prior to the Kyoto Protocol's expiration in 2012, the adopted recommendations of the Strategy Paper also point the way for international developments. The cornerstones of the package include setting a target for the reduction of greenhouse gas emissions, strengthening the emissions trading scheme, increasing energy efficiency, expanding the use of renewable energies, and increasing support for new technologies. What signals does this strategy send to other major industrialized countries and to the rapidly growing newly industrialized countries? How should it be evaluated in the context of the debate on a global climate regime after 2012 and given the alarming recent findings reported by the Intergovernmental Panel on Climate Change?
Keywords: 320